DNS blocking in KW: pornhub.com, tiktok.com, xvideos.com (Kuwait) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Kuwait. Data sourced from CensoredPlanet.
Censorship Incident ID: KW-2026-0003. Severity: critical. Confidence: 85%